Clinical pharmacokinetics and pharmacodynamics of artemisinin and derivatives. - White, N (1994)
Reliable and reproducible methods for the measurements of artemisinin and its derivatives in body fluids have proved difficult to develop. The available evidence suggests that all compounds are hydrolysed to a biologically active metabolite, dihydroartemisinin, which is eliminated rapidly. The role of other (hydroxylated) metabolites in humans requires further study. The hydrolysis of artesunate is so rapid that it may be considered a pro-drug for dihydroartemisinin. All the artemisinin compounds induce more rapid reduction of parasitaemia than other antimalarial drugs, indicating a direct effect on ring forms. This pharmacodynamic measure can be used in drug comparisons, and allows estimations of the number of parasites removed before sequestration.